Analisis Hubungan Kemampuan Pelayanan Kesehatan dengan Rate Rujukan Puskesmas di Wilayah Kerja BPJS Kesehatan Cabang Mataram Tahun 2024 - Asmara, I Made Adi Putra; Saimi, Saimi; Putri, Findi Dwi Ariestania; Swandayana, Putu Gede Wawan (Bioscientist : Jurnal Ilmiah Biologi, 2024)
This study aims to analyze the relationship between healthcare service capacity and referral rates at Puskesmas within BPJS Kesehatan Mataram Branch in 2024. This study used a correlation design with a cross-sectional approach. This design aims to evaluate the relationship between the service capabilities of health centers and referral rates at a certain time. The results of the study showed that Puskesmas with inpatient services tend to have safer referral rates compared to non-inpatient Puskesmas. Non-inpatient Puskesmas often refer more cases due to their limited capacity to manage complex cases at the primary level. The results emphasize the need for increased resources and medical training, especially in non-inpatient Puskesmas, to reduce unnecessary referrals to higher-level hospitals. Strengthening service capacity at Puskesmas is essential to ensure effective primary care and reduce the burden on referral hospitals.